1990
DOI: 10.1128/iai.58.2.412-415.1990
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of chitin in Pneumocystis carinii

Abstract: Polyclonal antisera against chitin and chitin oligomers were used to stain Pneumocystis carinii by the immunoperoxidase technique in Formalin-fixed, paraffin-embedded sections of four human lung biopsies and in alcohol-fixed, paraffin-embedded cell blocks of two bronchioloalveolar lavage specimens from infected human patients. In all cases, the antisera bound P. carinii but did not bind the host tissue elements. Moreover, the antisera bound not only to the cyst forms of P. carinii but also to the intracystic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The ␤-glucan appears to be necessary for viability since inhibitors of ␤-glucan synthetase can cure P. carinii pneumonia in animals (81,84). Other studies have reported the presence of material reactive with antibodies against chitin (32,110). Whatever its composition, the surface layer of trophic forms is insufficient to protect the cells from lysis under conditions that do not affect the integrity of conventional yeasts (41).…”
Section: P Carinii Is An Atypical Fungusmentioning
confidence: 99%
“…The ␤-glucan appears to be necessary for viability since inhibitors of ␤-glucan synthetase can cure P. carinii pneumonia in animals (81,84). Other studies have reported the presence of material reactive with antibodies against chitin (32,110). Whatever its composition, the surface layer of trophic forms is insufficient to protect the cells from lysis under conditions that do not affect the integrity of conventional yeasts (41).…”
Section: P Carinii Is An Atypical Fungusmentioning
confidence: 99%
“…Natural Ab to N ‐acetyl‐glucosamine, the sugar monomer of chitin, have been detected in various mouse strains with increased titers in aged mice 6. In addition, chitin‐specific Ab have been generated in rabbits 7. This demonstrates that the adaptive immune system can recognize and respond to chitin.…”
Section: Introductionmentioning
confidence: 98%
“…2 In addition, PC produces chitin in all three stages of its life cycle., i.e., cyst form, intracystic bodies, and trophozoites. 3 PC most commonly presents as pneumonia in patients with human immunodeficiency virus (HIV) infection. Extrapulmonary pneumocystosis is rare, and has been reported in lymph nodes, bone marrow, stomach, spleen, liver, small intestine, skin, pancreas, thyroid, choroid, and eye.…”
mentioning
confidence: 99%